KELIMPAHAN JENIS CORBICULA POSSOENSIS DAN MELANOIDES GRANIFERA (MOLUSKA) DI DANAU POSO, SULAWESI TENGAH - MUSTARIM SILUBA (BERITA BIOLOGI, 1987)
MUSTARIM SILUBA. 1987.Species abundance Corbicula possoensis and Melanoides granifera Mollusca) in Poso Lake, Central Sulawesi.Berita Bioiogi 3(7): 317 - 320. Corbicula possoensis and Meianoideu granifera are the two dominant species among 18 species of the mollusca that occured in poso Lake.The highly abundance of these two species distributed among three habitat types, i.e. sandy. mudsand, and gTavelly habitat. The study showed that the abundance of C. possoensis is 126,66/m2 in "sandy habitat, 118,66/m2 in mudsand habitat, and 51,00/m2 in gravelly habitat respectively. The abundance of M. granifera was lower then C. possoensis, i.e. 53,00/m2 in sandy habitat, 91.00/m2 in mudsand habitat, and 51,33/m2 in gravelly habitat. It is suggested that the references is done to their preference and their feeding technique.